2012
DOI: 10.1504/ijwi.2012.047995
|View full text |Cite
|
Sign up to set email alerts
|

Telework and mobile working: analysis of its benefits and drawbacks

Abstract: Telework and mobile work have been the object of much interest, but there has been little research on who practices it and what are the advantages. We evaluated the advantages and disadvantages for individuals in a large multinational in Belgium. In this organisation, telework is called 'mobile work', and includes not only telework at home but also work done at the client's office, in satellite offices, TeleCenters, etc. We observe that the technical possibility to do telework and gender are significantly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 22 publications
2
92
0
16
Order By: Relevance
“…Furthermore, the connection between flexible work practices (FWP) and the organizational attachment is mediated by the autonomy that employees might think they have regarding the structure and control of how, when, and where they can work [15]. A benefit of telework for both employees and employers consists in the increase in the flexibility and autonomy of workers [32,33]. Specifically, teleworkers own the freedom to organize their own activities and to decide where and how to work [6,34].…”
Section: Telework Work-life Balance and Teleworkers' Skillsmentioning
confidence: 99%
“…Furthermore, the connection between flexible work practices (FWP) and the organizational attachment is mediated by the autonomy that employees might think they have regarding the structure and control of how, when, and where they can work [15]. A benefit of telework for both employees and employers consists in the increase in the flexibility and autonomy of workers [32,33]. Specifically, teleworkers own the freedom to organize their own activities and to decide where and how to work [6,34].…”
Section: Telework Work-life Balance and Teleworkers' Skillsmentioning
confidence: 99%
“…More recently, a meta-analysis by Martin and MacDonnell (2012) found positive relationships between telework and organisational outcomes, including perceived productivity, improved retention and organisational commitment, and improved performance within the organisation. However, the literature suggests that not all telework arrangements are effective and that negative outcomes are observed under some conditions (Mahler, 2012;Sardeshmukh et al, 2012;Tremblay and Thomsin, 2012), including social isolation (Golden et al, 2008), co-worker dissatisfaction (Golden, 2007), and the so-called 'telework divide', where negative impacts have been observed for those barred from telework (Mahler, 2012). Moreover, telework appears to be a timedependent concept (Neufeld and Fang, 2005;B elanger et al, 2012), with negative effects observed in some studies where telework intensity exceeds two or three days per week (Gajendran andHarrison, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An extensive body of literature has looked into how working conditions have changed within organizations in the context of remote work (or telework). Remote work has been praised for a variety of reasons, from how it contributes to fostering organizational agility (Campbell and McDonald, 2009), to reducing organizational costs (Gregg, 2011), to enhancing flexibility and autonomy (Baruch, 2000;Pearlson and Saunders, 2001;Golden, 2009;Tremblay and Thomsin, 2012), to enabling employees to enact their own working times and spaces (Morgan, 2004;Gajendran and Harrison, 2007;Pyöriä, 2011), to improving work morale (Wheatley, 2012), amongst others. It has equally been criticized on many grounds, including the extent to which it can adversely affect knowledge sharing (Sarker et al, 2012), lead to instances of work intensification (Kelliher and Anderson, 2010) or hinder collaboration within an organization (Baruch, 2000;Pearlson and Saunders, 2001;Pyöriä, 2011).…”
Section: Individuals Organizations and New Work Configurationsmentioning
confidence: 99%
“…In particular, one can observe how new forms of collaboration are facilitated by recent technological innovations (Faraj et al, 2011). In addition, work is seen by many to no longer be bound to a particular place or time (Bosch-Sijtsema et al, 2010) and is, by extension, endowed with a greater sense of flexibility and autonomy (Baruch, 2000;Golden, 2009;Tremblay and Thomsin, 2012). Importantly, alongside these opportunities, come a series of concerns relating to issues of surveillance, control and, more generally, power dynamics (Sewell, 1998(Sewell, , 2012Brivot and Gendron, 2011).…”
Section: Introductionmentioning
confidence: 99%